PENGARUH KESIAPAN BELAJAR DAN KEPUASAN BELAJAR PADA PEMBELAJARAN ONLINE TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL - Nurdin Nurdin; Hery Purwosusanto Purwosusanto; tjipto djuhartono (Faktor Jurnal Ilmiah Kependidikan, 2022)
This study aims to analyze the influence of learning readiness and learning satisfaction on online learning on learning outcomes for the development of social science education. The research method is a survey, with a sample of 80 third semester students of postgraduate social studies study program at Indraprasta University, PGRI Jakarta. Data was collected using a questionnaire sent to students via email. The validity of the data with validity and reliability tests, all data have a normal distribution. Data were analyzed using correlation with the SPSS version 2.0 program. The results of the study indicate that learning readiness has a significant influence on learning outcomes for the development of social science education. Likewise, learning satisfaction in online learning has a significant influence on learning outcomes for the development of social science education. The research findings show that 75.2% of learning readiness and learning satisfaction in online learning have a strong relationship with learning outcomes for the development of social science education. This is because students are ready to take lessons well, as well as easy access to the internal network so that learning outcomes can be achieved well